A Decorated Portable Reliquarium from Shave Zion - Aviam, Mordechai; Shalem, Dina (Liber Annuus, 2012)
Abstract In a minor excavation at Shave Zion, the remains of a small structure with color mosaic floor were discovered. It was dated according to the pottery to the Byzantine period. As this is an isolated building atop a small hill, and as the direction of the mosaic decoration is facing east, it was suggested that these are remains of an ecclesiastic building, probably a monastery. At the edge of the site, a large portion of a stone reliquarium was discovered. Its small size, the decorations on its sides and the hole in its short side, point to the type of a “portable” reliquarium, which was carried by hands to enable pouring the oil from its interior into small bottles or ampoules.